Protons as Messengers of Intercellular Communication in the Nervous System - Soto, Enrique; Ortega-Ramírez, Audrey; Vega, Rosario (Frontiers in Cellular Neuroscience, 2018)
Several studies demonstrated that the low pH of synaptic vesicles implies that neurotransmitter release is always accompanied by the co-release of H+ into the synaptic cleft, leading to transient extracellular pH shifts. Also, evidence has accumulated indicating that various processes, including the activation of membrane transporters, increased production of CO2 and of metabolites, such as lactate, may produce significant extracellular pH shifts in nano- and micro-domains in the central nervous system (CNS), constituting a reliable signal for intercellular communication. The mechanisms modulating the proton concentration in such domains is complex and implies a source of protons in a network of transporters, ion exchangers and buffer capacity of the media may finally establish the extracellular proton concentration in the nano- or microdomains. Given that pH is a strictly regulated variable in multicellular organisms, localized pH changes may constitute significant signals of cellular processes that occur in a cell or a group of cells. The ASICs function as specific (not unique) signal sensors of this proton signaling mechanism, detecting subtle variations of extracellular H+ in a range varying from pH 5 to 8. The role of this signaling system in synaptic and extrasynaptic cellular communication constitutes an old evolutionary system that may have evolved from a metabolic state detection mechanism to a highly localized extracellular proton dependent communication mechanism. In this study evidence showing the mechanisms of regulation of extracellular pH shifts and of the ASICs and its function in modulating the excitability in various systems is reviewed, including data regarding its role in the neurotransmission. Finally, we here propose that protons constitute a relevant intercellular signaling mechanism whose regulatory mechanisms lead to differential responses to pH shifts.